Primary dyslipidemia and cardiometabolic risk: potential of pitavastatin - Berezin A.E.; Sheychenko T.V.; Berezina T.A.; Vishnevaya N.V.; Kovalenko N.V.; Kulik Z.I.; Мoiseenko I.А. (Medičnì Perspektivi)
The review is devoted to the most important aspects of primary mixed dyslipidemia treatment in patients at high risk with concomitant metabolic comorbidities. Evidences for novel modern approaches regarding primary prevention of cardiovascular events among dyslipidemic patients are considered. The potential role of lipid-lowering treatment with statins and their role in reducing the cardiovascular risk are discussed. Information about modern methods of minimization of residual cardiovascular risk using a combined lipid-lowering strategies and new representatives of the statins are provided. It has been discussed various strategies of statin administering to patients with dyslipidemia of different age with exiting comorbidities, such as diabetes mellitus, obesity, metabolic syndrome. Objective findings and treatment approaches obtained from the patient with obesity, metabolic syndrome, and asymptomatic atherosclerosis are provided. The role of pitavastatin in primary prevention program of cardiovascular events is discussed.